2015
DOI: 10.18632/oncotarget.3630
|View full text |Cite
|
Sign up to set email alerts
|

TOPK is highly expressed in circulating tumor cells, enabling metastasis of prostate cancer

Abstract: Circulating tumor cells (CTCs) are important for metastasis in prostate cancer. T-LAK cell-originated protein kinase (TOPK) is highly expressed in cancer cells. Herein, we established a xenograft animal model, isolated and cultured the CTCs, and found CTCs have significantly greater migratory capacity than parental cells. TOPK is more highly expressed in the CTCs than in parental cells and is also highly expressed in the metastatic nodules caused by CTCs in mice. Knocking down TOPK decreased the migration of C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
29
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 70 publications
0
29
0
Order By: Relevance
“…13 Sun et al 21 also reported that high-level expression of TOPK correlated with advanced stages of prostate cancer. 21 High TOPK expression is also associated with poor OS and PFS in early stages of ovarian cancer. 25 Using Kaplan-Meier analysis, furthermore, Joel et al 19 compared the OS between GBM patients with the highest (30%) and lowest (30%) expression levels of TOPK.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…13 Sun et al 21 also reported that high-level expression of TOPK correlated with advanced stages of prostate cancer. 21 High TOPK expression is also associated with poor OS and PFS in early stages of ovarian cancer. 25 Using Kaplan-Meier analysis, furthermore, Joel et al 19 compared the OS between GBM patients with the highest (30%) and lowest (30%) expression levels of TOPK.…”
Section: Discussionmentioning
confidence: 95%
“…Their hazard ratio is 2.13 (95%CI, 1.31–3.47) and 4.05 (95%CI, 2.24–7.03), respectively . Sun et al also reported that high‐level expression of TOPK correlated with advanced stages of prostate cancer . High TOPK expression is also associated with poor OS and PFS in early stages of ovarian cancer .…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…In colorectal cancer, increased levels of TOPK are correlated with high levels of interleukin-8 ( Xiao et al , 2015 ) and with oncogenic KRAS and BRAF mutations ( Zlobec et al , 2010 ). In prostate cancer, high TOPK expression correlates with increased invasiveness and cancer stage ( Sun et al , 2015 ). Conversely, low TOPK expression is predictive of poor prognosis in cholangiocarcinoma patients ( He et al , 2010 ).…”
mentioning
confidence: 99%